(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2018)
Giuseppe Zanoja’s poems have been published by Giuseppe Bossi in Milan in 1809. They have aroused a certain interest owing to the fact that some contemporary literati ascribed one of these compositions to Giuseppe Parini. This proves that his poems are good enough to be confused with those written by his prominent master, and justifies the necessity to produce a new edition of Zanoja’s poems based on manuscripts and printings in order to rediscover a not-well-known poet, who is nevertheless a significant figure within Parini’s school.